BOTANICAL EXTRACTS FOR THE TREATMENT OF ANDROGENETIC ALOPECIA: Pharmaceutical Science-Herbal Technology - MCCOY, JOHN; ZIERING, CRAIG (International Journal of Life Science and Pharma Research, 2012)
Androgenetic alopecia (AGA), commonly referred to as male or female pattern hair loss, affects approximately 50% of the population by the age of 50. While AGA is primarily a cosmetic condition, it is associated with aging and reduced virility and hence has negative psychological and social impact on patients. A number of treatments have been proposed for AGA, many originating from botanical extracts. Though, few of these treatments have undergone rigorous scientific scrutiny, years of empirical evidence often support their efficacy. In this study, we explored the use of lauric and myristic acid in the treatment of AGA. Gas chromatography and mass spectroscopy data taken from a representative sample of popular botanical treatments in Asia, revealed that lauric and myristic acid are the most commonly used botanicals for the treatment of AGA. We conducted a novel ex-vivo assay on surgically biopsied hair follicles to demonstrate the action of lauric and myristic acid on the biochemical pathways linked to AGA. Interestingly, we found evidence to support that the mechanism of action is not direct inhibition of 5α-reductase but instead a reduction of free testosterone.